Diastereoselective Synthesis of 1,3-syn-Oxazines via a Tandem Hemiaminalization and Tsuji–Trost Reaction - Tang, Bin; Wang, Liang; Menche, Dirk (Synlett, 2013)
A novel domino sequence for the rapid assembly of 1,3-syn-substituted oxazines is reported. Mechanistically, the one-pot procedure is based on a three-step sequential process involving a hemiaminalization and Tsuji–Trost reaction. The process generates up to two new stereogenic centers in a concise and convergent fashion from simple and readily available starting materials.
Keywords: synthetic methodology; tandem reaction; catalysis; allylic substitution; oxazines